2006
DOI: 10.1074/jbc.m602957200
|View full text |Cite
|
Sign up to set email alerts
|

The Globular Tail Domain of Myosin Va Functions as an Inhibitor of the Myosin Va Motor

Abstract: The actin-activated ATPase activity of full-length mammalian myosin Va is well regulated by Ca 2؉ , whereas that of truncated myosin Va without the C-terminal globular tail domain (GTD) is not. Here, we have found that exogenous GTD is capable of inhibiting the actin-activated ATPase activity of GTDdeleted myosin Va. A series of truncated constructs of myosin Va further showed that the entire length of the first coiled-coil (coil-1) of the tail domain is critical for GTD-dependent regulation of myosin Va and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
118
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(125 citation statements)
references
References 34 publications
4
118
0
3
Order By: Relevance
“…3, A and B; Supplemental Movies S1 and S3; data not shown). This result indicated that the XI-K tail-mediated suppression of Golgi trafficking did not require IQ or coiled-coil motifs and was likely dependent on interference with cargo binding rather than tail-mediated inhibition of the motor domain given that the latter tail activity was shown to require the coiled-coil region (Li et al, 2006).…”
Section: Isolation Of Myosin Cdnas From N Benthamiana and Phylogenetmentioning
confidence: 69%
“…3, A and B; Supplemental Movies S1 and S3; data not shown). This result indicated that the XI-K tail-mediated suppression of Golgi trafficking did not require IQ or coiled-coil motifs and was likely dependent on interference with cargo binding rather than tail-mediated inhibition of the motor domain given that the latter tail activity was shown to require the coiled-coil region (Li et al, 2006).…”
Section: Isolation Of Myosin Cdnas From N Benthamiana and Phylogenetmentioning
confidence: 69%
“…Later, it was found that the GTD directly inhibits the activity of the motor domain of myosin-Va: Myosin-Va HMM is inhibited and folded by exogenous GTD (9,10). We found that strong inhibition of motor activity by the GTD requires not only the two-headed structure, but also the presence of an intact first long coiled-coil segment of the tail (9).…”
mentioning
confidence: 94%
“…We found that strong inhibition of motor activity by the GTD requires not only the two-headed structure, but also the presence of an intact first long coiled-coil segment of the tail (9). Based on these findings, we proposed that the GTD simultaneously binds to the motor domain and the C terminus of the first long coiled-coil segment of the tail, thus forming a triangular conformation (9). However, the precise interaction between the GTD and the motor domain and thus the mechanism of inhibition remained unclear.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…However, if all the coiled-coil domains and the inter-coiled-coil regions were in an extended conformation, the length of the neck domains would not allow the heads to reach the GTDs. Indeed, the GTDs were shown to interact with the C-terminal part of the proximal coiled-coil region, and this interaction was proved to be necessary for the binding of the heads in the inactive conformation (68). It is obvious that the direction of the myosin 5a heavy chains must be totally reversed in this conformation to allow the GTDs to reach the proximal coiled-coil.…”
Section: Discussionmentioning
confidence: 99%